2011
DOI: 10.1155/2011/261453
|View full text |Cite
|
Sign up to set email alerts
|

Modern Contraceptive and Dual Method Use among HIV-Infected Women in Lusaka, Zambia

Abstract: HIV-infected women in sub-Saharan Africa are at substantial risk of unintended pregnancy and sexually transmitted infections (STIs). Linkages between HIV and reproductive health services are advocated. We describe implementation of a reproductive health counseling intervention in 16 HIV clinics in Lusaka, Zambia. Between November 2009 and November 2010, 18,407 women on antiretroviral treatment (ART) were counseled. The median age was 34.6 years (interquartile range (IQR): 29.9–39.7), and 60.1% of women were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
62
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 16 publications
25
62
7
Order By: Relevance
“…Free discussion with partner as well as with health professional and receiving counseling about dual contraceptive methods are associated with current dual contraceptive method utilization practice .HIV positive women who have open discussion with partner use dual contraceptive methods ten times more than women who have no discussion with their partners. This finding is similar with finding from Soweto South Africa and Lusaka Zambia [12,13], Uganda [10] and Adwa northern Ethiopia [14]. Most of the respondents in in-depth interview mentioned that even if they know the benefits of dual contraceptive method utilization and they wanted to use it, their partners were not volunteers to use it.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Free discussion with partner as well as with health professional and receiving counseling about dual contraceptive methods are associated with current dual contraceptive method utilization practice .HIV positive women who have open discussion with partner use dual contraceptive methods ten times more than women who have no discussion with their partners. This finding is similar with finding from Soweto South Africa and Lusaka Zambia [12,13], Uganda [10] and Adwa northern Ethiopia [14]. Most of the respondents in in-depth interview mentioned that even if they know the benefits of dual contraceptive method utilization and they wanted to use it, their partners were not volunteers to use it.…”
Section: Discussionsupporting
confidence: 83%
“…The finding of the study showed that 48 (19.8%) of the participants reported using dual-contraceptive methods currently and the finding is almost similar with finding from cohort study conducted on HIV Seropositive women in Lusaka Zambia 17.7% however, less than a crosssectional survey result in Soweto, South Africa on HIV-positive women which is (33%) [12,13].…”
Section: Discussionsupporting
confidence: 74%
“…30 This finding however should be taken with concern, mainly because the usual assumption is that single and widowed women are not in need for contraceptive methods, yet the truth is that they may be engaging in unprotected sexual encounters, putting them at risk of STIs or unplanned pregnancies. 31 They therefore represent a vulnerable group in need of a direct and specific intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Women who have more numbers of children are more likely to use modern contraceptives. Some studies argued that as women's age increase the likelihood to use modern contraceptive decrease [28].…”
mentioning
confidence: 99%